Recent advancements in multifaceted roles of flavonoids in plant–rhizomicrobiome interactions - Kumar, Gokul Anil; Kumar, Sumit; Bhardwaj, Rupesh; Swapnil, Prashant; Meena, Mukesh; Seth, Chandra Shekhar; Yadav, Ankush (Frontiers in Plant Science, 2024)
The rhizosphere consists of a plethora of microbes, interacting with each other as well as with the plants present in proximity. A variety of plant-microbe interactions have been studied vividly in the rhizosphere niche. The plant-microbe interactions in this particular niche are characterized by the secretion of specific secondary metabolites through root exudation which help in host-bacteria communication and association. The root exudates consist of a variety of secondary metabolites such as strigolactones and other phenolic compounds such as coumarin that helps in facilitating communication and forming associations with beneficial microbes in the rhizosphere. Among different secondary metabolites flavonoids (natural polyphenolic compounds) continuously increasing attention in scientific fields for showing several slews of biological activities. Flavonoids possess a benzo-γ-pyrone skeleton and several classes of flavonoids have been reported on the basis of their basic structure such as flavanones, flavonols, anthocyanins, etc. The mutualistic association between plant growthpromoting rhizobacteria (PGPR) and plants have been reported to help the host plants in surviving various biotic and abiotic stresses such as low nitrogen and phosphorus, drought and salinity stress, pathogen attack, and herbivory. This review sheds light upon one such component of root exudate known as flavonoids, which is well known for nodulation in legume plants. Apart from the well-known role in inducing nodulation in legumes, this group of compounds has anti-microbial and antifungal properties helping in establishing defensive mechanisms and playing a major role in forming mycorrhizal associations for the enhanced acquisition of nutrients such as iron and phosphorus. Further, this review highlights the role of flavonoids in plants for assisting the plants to recruit beneficial non-mutualistic microbe for helping the plants cope with therecruiting non-mutualistic microbes under stress . This paper also covers variousand other important aspects regarding recent findings on the functions of this secondary metabolite in guiding the plant-microbe interaction and how organic matter affects its functionality in soil.